The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1007/bf02538083
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in gap junction assembly and function

Abstract: Gap junctions (GJ) are important regulators of cellular function. They provide channels for the direct movement of small molecules between cells and thus control cell-to-cell transfer of metabolites and the transmission of various stimuli. Gap junctions have been shown to be involved in a multitude of cellular processes ranging from cell synchronization and neuronal function to cell differentiation and carcinogenesis. Much knowledge has been gained in recent years concerning the structure and molecular organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 99 publications
0
38
0
Order By: Relevance
“…The cholesterol enrichment of cell membranes after dietary hypercholesterolemia may alter the assembly and distribution of Cx43. 41 Meyer et al 42 have treated cells with cholesterol in serum-free media and observed a decrease in gap junction assembly. The dietary hypercholesterolemia, increasing nonspecific effectors of inflammation 43 and the oxidative stressdependent processes of macrophages within the myocardium, 44 was shown to activate JNK in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol enrichment of cell membranes after dietary hypercholesterolemia may alter the assembly and distribution of Cx43. 41 Meyer et al 42 have treated cells with cholesterol in serum-free media and observed a decrease in gap junction assembly. The dietary hypercholesterolemia, increasing nonspecific effectors of inflammation 43 and the oxidative stressdependent processes of macrophages within the myocardium, 44 was shown to activate JNK in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have shown that the lipid content of the plasma membrane, as well as the extracellular space, have diverse effects on gap junctions. 22 In animal studies investigating the effect of hyperlipidemia on endothelial gap junctions, a recent ultrastructural study reported that fewer aortic endothelial gap junctions were present in rats fed a long-term, cholesterolenriched diet compared with those fed normal chow. 6 However, because immunohistochemical examination was not conducted in that study, the details of the component connexins remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Specific lipids, such as cholesterol and low-density lipoprotein, also appear to be required for and modulate the efficiency of channel assembly. Both inhibitory as well as stimulatory effects have been reported, depending upon the concentrations used (Malewicz et al, 1990;Meyer et al, 1990). Finally, alkaline extracellular pH promotes junctional communication between oocyte pairs , presumably by interacting with intrinsic determinants (cysteine residues on the extracellular loops of connexins, see below).…”
Section: Docking and Gatingmentioning
confidence: 99%